EFEK MEDIA PEMBELAJARAN VIRTUAL PHET TERHADAP HASIL BELAJAR IPA SISWA - Simbolon, Dedi Holden; Pardede, Eni Yusnita Br; Perbina, Theresia; Manik, Alena Rosiana (Unversitas Katolik Santo Thomas, 2025)
This study aims to examine the effect of using PhET Interactive Simulations as a virtual learning medium on students’ science learning outcomes in senior high school. A quasi-experimental method with a pretest-posttest control group design was employed. The sample consisted of two randomly selected Grade XI classes, one assigned as the experimental group (using PhET) and the other as the control group (using conventional instruction). The research instrument was an essay test comprising 10 items, which had been validated and tested for reliability (KR-20 = 0.78). Data were analyzed using the Shapiro-Wilk test for normality, Levene’s test for homogeneity, paired sample t-test, and independent sample t-test. The results showed a significant improvement in science learning outcomes for the experimental group, with an average pretest score of 28.00 increasing to 57.41 in the posttest. The paired t-test revealed a significance value of 0.000 (p < 0.05), and the normalized gain score was 0.40, indicating a moderate level of effectiveness. These findings suggest that the PhET-based virtual learning media effectively enhances students' conceptual understanding in science, supporting active, constructivist learning principles in line with the Indonesian